Probiotic Properties of Lactic Acid Bacteria Isolated From Neera: A Naturally Fermenting Coconut Palm Nectar - Somashekaraiah, Rakesh; Shruthi, B.; Deepthi, B. V.; Sreenivasa, M. Y. (Frontiers in Microbiology, 2019)
Probiotic bacteria were isolated from different traditional fermented foods as, there are several such foods which are not well explored for their probiotic activities. Hence the present study was conducted to find the potential of lactic acid bacteria (LAB) as probiotics which were isolated from the sap extract of the coconut palm inflorescence – Neera, is a naturally-fermented drink consumed in various regions of India. A total of 75 isolates were collected from the Neera aseptically in the early morning (before sunrise). These isolates were initially screened for cultural, microscopic and biochemical characteristics. The initial screening yielded 40 Gram-positive, catalase-negative isolates that were further subjected to acid–bile tolerance with resistance to phenol. Among 40 isolates, 16 survived screening using analysis of cell surface hydrophobicity, auto aggregation with adhesion to epithelial cells and gastric–pancreatic digestion for gastrointestinal colonization. The isolates were also assessed for antimicrobial, antibiotic sensitivity and anti-oxidative potential. The safety of these isolates was evaluated by their haemolytic and deoxyribonuclease (DNAse) activities. Based on these results, seven isolates with the best probiotic attributes were selected and presented in this study. These LAB isolates, with 51.91–70.34 % survival at low pH, proved their resistance to gastric conditions. The cell surface hydrophobicity of 50.32–77.8 % and auto aggregation of 51.02–78.95 % represented the adhesion properties of these isolates. All the seven isolates exhibited good antibacterial and antifungal activity, showing hydroxyl-scavenging activity of 32.86–77.87 %. The results proved that LAB isolated from Neera exhibited promising probiotic properties and seem favorable for use in functional fermented foods as preservatives.